Teologi Misi Lintas Budaya Di Indonesia - Paath, Jeane; Harefa, Febriaman Lalaziduhu (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2025)
This research aims to develop mission theology within the context of cross-cultural engagement in Indonesia, a multicultural country rich in diverse traditions and local values. The employed method is qualitative, utilizing a literature review that involves analyzing missiological thought and the practical experiences of missionaries. The findings indicate that a contextual approach that integrates local culture with the teachings of the Gospel can enrich the spiritual experience of congregations. This study emphasizes the importance of collaboration between the church and the community, as well as the use of modern technology in evangelism. The conclusion of this research is that a holistic and integrative mission theology can address cultural and social challenges in the era of globalization, making evangelism a relevant and sustainable participatory process.